Virtual Dissection: Emerging as the Gold Standard of Analyzing Living Heart Anatomy - Justin T. Tretter (Journal of Cardiovascular Development and Disease, 2020)
: Traditionally, gross cardiac anatomy has been described mainly based on the findings in the dissection suite. Analyses of heart specimens have contributed immensely towards building a fundamental knowledge of cardiac anatomy. However, there are limitations in analyzing the autopsied heart removed from the thorax. Three-dimensional imaging allows visualization of the blood-filled heart in vivo in attitudinally appropriate fashion. This is of paramount importance for not only demonstration of cardiac anatomy for educational purposes, but also for the detailed anatomical evaluation in patients with acquired and congenital heart disease. In this review, we discuss the advantages of three-dimensional imaging, specifically focusing on virtual dissection, a volume rendering-based reconstruction technique using computed tomographic data. We highlight examples of three-dimensional imaging in both education and guiding patient management.